Computer simulations of the influence of geometry in the performance of conventional and unconventional lithium-ion batteries. (1st March 2016) - Miranda, D.; Costa, C.M.; Almeida, A.M.; Lanceros-Méndez, S.
Highlights: The influence of geometries in lithium-ion battery performance is analyzed. Conventional and unconventional battery geometries are investigated. Unconventional geometries include horseshoe, spiral, ring, antenna and gear batteries. The best capacity value at 330 C is obtained for the interdigitated geometry. The capacity value is dependent on thickness and collectors position. Abstract: In order to optimize battery performance, different geometries have been evaluated taking into account their suitability for different applications. These different geometries include conventional, interdigitated batteries and unconventional geometries such as horseshoe, spiral, ring, antenna and gear batteries. The geometry optimization was performed by the finite element method, applying the Doyle/Fuller/Newman model. At 330 C, the capacity values for conventional, ring, spiral, horseshoe, gear and interdigitated geometries are 0.58 A h m −2, 149 A h m −2, 182 A h m −2, 216 A h m −2, 289 A h m −2 and 318 A h m −2, respectively. The delivered capacity depends on geometrical parameters such as maximum distance for the ions to move to the current collector, d _max, distance between of current collectors, d _cc, as well as the thickness of separator and electrodes, allowing to tailor battery performance and geometry for specific applications.